Memory and Identity in Margaret Atwood´s Cat´s Eye - Karásková, Vendula (Univerzita Pardubice, 2012)
The main aim of this paper is the analysis of the novel Cat's Eye by Margaret Atwood. The theoretical part provides readers with historical and cultural context of the novel - it is focused on the role of women in the 1940s and 1950s society, on second wave feminism in the 1960s and it explains the term identity which is crucial for the analytical part of the paper. The second part of the paper tries to trace back the reasons of identity crisis of the main protagonist of the novel. The main aim is to examine identity development of the main character with the analysis of the main character's memories.
Paměť a identita v díle Kočičí oko od Margaret Atwood
Keywords: Kočičí oko; postavení žen ve společnosti; druhá vlna feminismu; identita; Atwood, Margaret; Cat's Eye; roles of women in society; second wave feminism; identity